ANALISIS KEMAMPUAN MEMBACA SISWA KELAS IV DALAM PEMBELAJARAN BAHASA INDONESIA DI SDN 182/1 HUTAN LINDUNG - Najwa Azzahra, Nabilla; Desta Widyawati, Arum; Juita Ananda, Ivta; Khoirunnisa; Silvina Noviyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the reading ability of fourth-grade students in Indonesian Language learning at SDN 182/1 Hutan Lindung. The background of this research is the discovery of students who have difficulty maintaining reading concentration, differences in individual reading speed, and the impact of reading ability gaps on classroom learning dynamics. This study uses a descriptive qualitative approach with data collection techniques according to Creswell, including observation, interviews, and documentation. The data source of this study is the fourth-grade teacher of SDN 182/1 Hutan Lindung as the main informant. Interviews were conducted using semi-structured techniques based on 12 systematically prepared questions. The results show that in general, the reading ability of fourth-grade students is in the good category, with an achievement of around 80 percent. The main obstacles found in the field are difficulty in maintaining students' concentration during sustained reading sessions, significant differences in reading speed between individuals, and there are still students who read more slowly than their peers. Alternative solutions offered include the application of gamification methods, timed reading techniques, differentiated learning, and structured follow-up reflections. This research is expected to provide a real contribution to improving the quality of reading learning in fourth grade elementary school.